2003
DOI: 10.1021/es034252m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Methylmercury on Reproductive Endocrinology of Fathead Minnows

Abstract: Recent laboratory studies have demonstrated that environmentally realistic concentrations of dietary methylmercury can impair reproduction of fish. To evaluate relations between reproductive success and biomarkers of methylmercury exposure, we fed juvenile fathead minnows (Pimephales promelas) one of three diets contaminated with methylmercury: 0.06 (control), 0.87 (low), and 3.93 (medium) microg of Hg g(-1) dry weight. At sexual maturity, fish were paired, allowed to reproduce, and then analyzed for total mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 40 publications
11
120
0
Order By: Relevance
“…The histological observation revealed that MMC treatment has comparatively overt bad effects on male medaka gonads, which indicated that MMC pollution might damage fish's reproductive system, thus leading to the procreation failure of the fish. Similar histopathological patterns found in other reports Canton, 1991, 1992;Drevnick and Sandheinrich, 2003) confirmed the results obtained above. A study concerning specific effects of various environmental pollutants including MeHg on the reproductive system of small freshwater fish species guppy (Poecilia reticulata) and medaka (Oryzias latipes) suggested that 1.8 ng/mL of MeHg induced the impairment of spermatogenesis (Wester and Canton, 1991).…”
Section: Male Gonadsupporting
confidence: 92%
See 1 more Smart Citation
“…The histological observation revealed that MMC treatment has comparatively overt bad effects on male medaka gonads, which indicated that MMC pollution might damage fish's reproductive system, thus leading to the procreation failure of the fish. Similar histopathological patterns found in other reports Canton, 1991, 1992;Drevnick and Sandheinrich, 2003) confirmed the results obtained above. A study concerning specific effects of various environmental pollutants including MeHg on the reproductive system of small freshwater fish species guppy (Poecilia reticulata) and medaka (Oryzias latipes) suggested that 1.8 ng/mL of MeHg induced the impairment of spermatogenesis (Wester and Canton, 1991).…”
Section: Male Gonadsupporting
confidence: 92%
“…las) indicated that reproduction of wild fishes may be adversely affected by methylmercury and that suppressed hormone levels may be used to indicate diminished reproduction of fish (Drevnick and Sandheinrich, 2003).…”
Section: Male Gonadmentioning
confidence: 99%
“…Elevated levels of contaminants, including chlorinated hydrocarbons, in several other fish species are associated with reproductive impairment (Cameron et al 1992;Drevnick and Sandheinrich 2003;Hammerschmidt et al 2002;Longwell et al 1992), reduced egg viability (Billsson et al 1998;Giesy et al 1986;Mac and Edsall 1991;Matta et al 1997;Von Westernhagen et al 1981), reduced survival of larval fish (Berlin et al 1981;Giesy et al 1986), delayed maturity (Jorgensen et al 2004) and posterior malformations (Billsson et al 1998). Pesticide exposure in fish may affect antipredator and homing behavior, reproductive function, physiological development, and swimming speed and distance (Beauvais et al 2000;Moore and Waring 2001;Scholz et al 2000;Waring and Moore 2004).…”
Section: Marine Pollution and Environmental Contaminationmentioning
confidence: 99%
“…Juvenile grayling (Thymallus thymallus) containing wholebody concentrations of 0.27 Ag/g resulting from dietary methylmercury exposure experienced permanent impairment of feeding efficiency and competitive ability (Fjeld et al, 1998). In female fathead minnows (Pimephales promelas), dietary methylmercury concentrations of 0.87 Ag/g dw (about 0.17 Ag/g ww assuming 80% moisture) increased whole-body Hg concentrations by more than 10-fold, suppressed hormone levels, and inhibited gonadal development relative to controls (Drevnick and Sandheinrich, 2003). It therefore appears that the greatest concentrations observed in fish from the RGB (~0.5 Ag/g) may be sufficiently high to represent a risk to the fish themselves.…”
Section: Exposure Indicatorsmentioning
confidence: 99%